2016
DOI: 10.1016/j.tox.2016.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Translational potential of long-term decreases in mitochondrial lipids in a mouse model of Gulf War Illness

Abstract: Gulf War Illness (GWI) affects 25% of veterans from the 1990-1991 Gulf War (GW) and is accompanied by damage to the brain regions involved in memory processing. After twenty-five years, the chronic pathobiology of GWI is still unexplained. To address this problem, we examined the long-term consequences of GW exposures in an established GWI mouse model to identify biological processes that are relevant to the chronic symptoms of GWI. Three-month old male C57BL6 mice were exposed for 10days to GW agents (pyridos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 61 publications
(76 reference statements)
5
43
2
Order By: Relevance
“…A study by Koslik et al (2014) demonstrated mitochondrial dysfunction in the calf muscle of patients with GWI. Another study using a mouse model of GWI showed decreased levels of mitochondrial lipids in the brain, implying the reduced activity of electron transport chain (Abdullah et al, 2016), which contradicts the hyperactive mitochondrial respiration suggested by the current findings. The discrepancy between the studies could be attributed to the different time-points of investigation (i.e., at 15–16 months post-exposure in Abdullah et al, 2016 vis-à-vis 6 months post-exposure in the current study, respectively).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…A study by Koslik et al (2014) demonstrated mitochondrial dysfunction in the calf muscle of patients with GWI. Another study using a mouse model of GWI showed decreased levels of mitochondrial lipids in the brain, implying the reduced activity of electron transport chain (Abdullah et al, 2016), which contradicts the hyperactive mitochondrial respiration suggested by the current findings. The discrepancy between the studies could be attributed to the different time-points of investigation (i.e., at 15–16 months post-exposure in Abdullah et al, 2016 vis-à-vis 6 months post-exposure in the current study, respectively).…”
Section: Discussioncontrasting
confidence: 99%
“…Another study using a mouse model of GWI showed decreased levels of mitochondrial lipids in the brain, implying the reduced activity of electron transport chain (Abdullah et al, 2016), which contradicts the hyperactive mitochondrial respiration suggested by the current findings. The discrepancy between the studies could be attributed to the different time-points of investigation (i.e., at 15–16 months post-exposure in Abdullah et al, 2016 vis-à-vis 6 months post-exposure in the current study, respectively). It is plausible that mitochondrial electron transport chain initially responds to neurotoxic exposure with hyperactivity, following which the generation of increased amounts of ROS, damages the electron transport chain over a period of time, eventually leading to its reduced activity.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The Folch extraction of serum and plasma samples was performed as previously described [66-68] using the Folch method [69] following an addition of di-14:0 fatty acid (FA) containing PC and PE (Matreya, Pleasant Gap, PA), di-16:0 PI, and 14:0 LPC (Avanti, Albaster, AL) as internal standards. High-pressure liquid chromatography (HPLC) was achieved using a 1mm ID x 10 cm column containing Pinnacle II 3 μm silica particles (Restek, Bellefonte, PA, USA).…”
Section: Methodsmentioning
confidence: 99%